If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4(4x + 1) = 2x + -4(6 + -1x) + 8 Reorder the terms: 4(1 + 4x) = 2x + -4(6 + -1x) + 8 (1 * 4 + 4x * 4) = 2x + -4(6 + -1x) + 8 (4 + 16x) = 2x + -4(6 + -1x) + 8 4 + 16x = 2x + (6 * -4 + -1x * -4) + 8 4 + 16x = 2x + (-24 + 4x) + 8 Reorder the terms: 4 + 16x = -24 + 8 + 2x + 4x Combine like terms: -24 + 8 = -16 4 + 16x = -16 + 2x + 4x Combine like terms: 2x + 4x = 6x 4 + 16x = -16 + 6x Solving 4 + 16x = -16 + 6x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-6x' to each side of the equation. 4 + 16x + -6x = -16 + 6x + -6x Combine like terms: 16x + -6x = 10x 4 + 10x = -16 + 6x + -6x Combine like terms: 6x + -6x = 0 4 + 10x = -16 + 0 4 + 10x = -16 Add '-4' to each side of the equation. 4 + -4 + 10x = -16 + -4 Combine like terms: 4 + -4 = 0 0 + 10x = -16 + -4 10x = -16 + -4 Combine like terms: -16 + -4 = -20 10x = -20 Divide each side by '10'. x = -2 Simplifying x = -2
| 9x^5+9x-63= | | 4-3m=30 | | 4+2z-3=9z+6-6z | | -49=6c-13-14 | | 198=28*a+140*b | | .5x-4=.3x+1 | | 10x-9x= | | h=-16t^2+285 | | 60*(24.95*.6)+3+(59*.75)= | | 3x+x-5=x-3 | | 98=7*a+b*28 | | x-4(x+30)=24 | | 2n-10=x+20 | | 3(5x-2)+4(17-2x)-2(3x+1)=-1 | | 13x+17-4x=24 | | 19-2x-3=2x+3+x | | 2(x+1)=8(x-3)-10 | | 4y-3x-8=0 | | 8.3=4.1+10.5 | | 4y-6(y+4)=1-y | | 21a+21=28a+14 | | 5sinx-8cosx=6 | | 4(-5+x)=5x+.5 | | 2x^2+4x+4=20 | | .66666666666666(4x-5)=8 | | 18-(5m+8)=5+4m-13 | | 3x-5=7x+2-3 | | (4x-5)+(2x+20)=45 | | 6x+x-0.9=6x+0.9 | | -3-6X=28 | | X+65X+1000=0 | | (18)-2y-4= |